Mike, help me!: um jogo para apoio ao processo de ensino-aprendizagem de técnica de especificação de requisitos de software - Venâncio, João Vítor D.; Benitti, Fabiane B. V. (Anais do Workshop sobre Educação em Computação (WEI), 2023)
Requirements Engineering is a critical phase in the software development process that focuses on identifying, analyzing, documenting, and managing software requirements.. Research shows that most software project failures are due to requirements engineering issues. Thus, we propose a solution for the active learning of requirements specification techniques. Considering that the user story technique is currently well accepted by IT companies, this paper proposes a mobile game that supports learning and practice in writing user stories. As a result, the game proved to help in learning user stories and some of their quality criteria, in addition to presenting good usability as a product.